The assembly sequences modeling using graph incidence matrix - I. A. Volkov; D. D. Primak; V. B. Masyagin; R. L. Artykh (Омский научный вестник)
The article discusses the problem solution of computer aided determination of the precision axisymmetric products assembly sequence. The aim of this work is to consider the possibility of using a directed assembly graph, in particular, an adjacency matrix and an incidence matrix in the theoretical description of the construction and design of the assembly technology. This approach corresponds to solving the problem in mathematical form. The analysis of the features of mathematical modeling of the construction and the assembly process is performed. The method for constructing a graph that displays the relationships between parts and the assembly process is proposed. Implementation the task of automated formation the assembly process is performed using algorithms and a computer program based on the matrix representation of graphs. A comparative analysis of the results obtained theoretically and using computer in the framework of assembly processes design is performed. The obtained results makes it possible to quickly enter the necessary changes in assembly sequence, thereby possibility emerges of monitoring data and decisions when designing assembly processes.